2019
DOI: 10.1084/jem.20190678
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant PIK3CD and TNFRSF9 deficiencies cause chronic active Epstein-Barr virus infection of T cells

Abstract: Infection of T cells by Epstein-Barr virus (EBV) causes chronic active EBV infection (CAEBV) characterized by T cell lymphoproliferative disorders (T-LPD) of unclear etiology. Here, we identified two homozygous biallelic loss-of-function mutations in PIK3CD and TNFRSF9 in a patient who developed a fatal CAEBV. The mutation in TNFRSF9 gene coding CD137/4-1BB, a costimulatory molecule expressed by antigen-specific activated T cells, resulted in a complete loss of CD137 expression and impaired T cell expansion to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
70
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(72 citation statements)
references
References 58 publications
2
70
0
Order By: Relevance
“…Therefore, the signal induced by half of CD70 receptors on the surface of LCL seems sufficient to maintain an efficient immune response to EBV. It is likely, that other receptors from the TNFR superfamily, like CD137/CD137L, deliver EBV-specific T cell cosignals required for their expansion (21).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the signal induced by half of CD70 receptors on the surface of LCL seems sufficient to maintain an efficient immune response to EBV. It is likely, that other receptors from the TNFR superfamily, like CD137/CD137L, deliver EBV-specific T cell cosignals required for their expansion (21).…”
Section: Discussionmentioning
confidence: 99%
“…9 This phenotype was also observed in the two patients analyzed by Rodriguez et al, where memory B cell numbers were severely reduced. 10 Although B cell subsets were not analyzed by Alosaimi et al, low IgG and high IgM levels, and a poor antibody response to tetanus toxoid and an absent recall response to pneumococcal polysaccharide vaccine, in one of the two patients indicate a disturbance in B cell maturation. Somekh et al also analyzed Tfh numbers and found reduced counts in 3 of the 4 patients.…”
mentioning
confidence: 93%
“…The authors conclude that the lack of CD137 costimulation prevented the clearance of EBV-infected T cells. 10 Two of the four patients analyzed by Somekh et al suffered from an EBV-related B cell lymphoma, Hodgkin's lymphoma (HL) and Burkitt's lymphoma, respectively, and one patient described by Alosaimi et al presented with HL. 8,9 One patient analyzed by Rodriguez et al suffered from EBV-associated T cell lymphoproliferative disease, and finally succumbed to hemophagocytic lymphohistiocytosis (HLH).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The only relevant natural ligand so far discovered is 4-1BBL, which forms trimers on the membrane of mature macrophages, dendritic cells, and activated B cells (Croft et al, 2013). The key role of 4-1BB costimulation in CTL biology is best perceived considering the phenotype of CD137 −/− mice upon viral infection (Wortzman et al, 2013) and the alterations in the control of herpes viruses such as Epstein-Barr in patients with homozygous CD137 mutations (Rodriguez et al, 2019). Simple experiments in transplantable tumor models indicated that rejection of established tumors can be elicited by systemic administration of agonist anti-4-1BB mAb (Melero et al, 1997).…”
mentioning
confidence: 99%